Gestão de pessoas no ministério de Paulo em Éfeso (Atos 19.1-10) - Faustini, Silvio Junior (2011)
The purpose of this research paper is to identify a biblical model that describes the existence of a People Management (PM) method in Paul s ministry at Ephesus. To achieve this end, we established the following specific goals: What is PM? What is the real meaning or the correct interpretation of Acts 19.1-10? According to the text and its context, is it possible to identify a leadership management and training process during Paul s stay in Ephesus? These questions and basic objectives shape the research as follows: The first part addresses: the historic phases and progression of PM; its conceptual premises, explaining with details what they are; its main objectives in relation to people management; and the processes used to implement it in the context of organizations. Ten arguments supporting the relevance of PM in church end this first part. It would be good to point out that the APPENDIX I (historical critical exegesis of Acts 19.1-10) included in this research paper seeks to substantiate the affirmations made in the second chapter and point out the biblical model of PM in Paul s ministry. Historical critical exegesis is one of the most common procedures in diachronic analysis of the Bible, and submits the selected text to forty distinct stages, which in turn, permit different viewpoints and allow an exact, deep and wide interpretation of the selected text. The second and last chapters are based on the conceptual elements of the first chapter and link these with the exegesis (Acts 19.1-10) didactically building a bridge between Paul s actions in Ephesus and the process of 21st century PM. This last part ends with the identification of three of Paul s skills in the process of aggregating, applying and enabling people to exercise Christian service. Within this perspective, this work intends to provoke thought and provide tools to make PM implementation viable in the current ecclesiastical context. It is believed that PM can align the interests of the church with those of its collaborators and encourage greater interdependence between both.